Research on development path of China's energy finance in the era of big data - Cheng, Jia-ning (IJRDO - Journal of Business Management, 2021)
The arrival of the era of big data highlights the importance of information competition and network advantages, promotes the theoretical innovation of energy finance, and provides a new analysis tool for energy finance market. China's energy finance faces new challenges in market design, transaction mode and risk monitoring. On the basis of analyzing the development problems of energy finance in China, this paper discusses the new development path of energy finance in China, so as to play an important role in the global energy finance system.